Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To estimate the solution to the given system of equations:
[tex]\[ \left\{\begin{array}{l} 7 x - y = 7 \\ x + 2 y = 6 \end{array}\right. \][/tex]
Let's solve the equations step by step.
### Step 1: Solve one of the equations for one variable
Let's solve the second equation for [tex]\( x \)[/tex]:
[tex]\[ x + 2y = 6 \][/tex]
[tex]\[ x = 6 - 2y \][/tex]
### Step 2: Substitute the expression into the other equation
Now, substitute [tex]\( x = 6 - 2y \)[/tex] into the first equation:
[tex]\[ 7(6 - 2y) - y = 7 \][/tex]
[tex]\[ 42 - 14y - y = 7 \][/tex]
[tex]\[ 42 - 15y = 7 \][/tex]
### Step 3: Solve for [tex]\( y \)[/tex]
[tex]\[ 42 - 15y = 7 \][/tex]
[tex]\[ -15y = 7 - 42 \][/tex]
[tex]\[ -15y = -35 \][/tex]
[tex]\[ y = \frac{-35}{-15} \][/tex]
[tex]\[ y = \frac{35}{15} \][/tex]
[tex]\[ y = \frac{7}{3} \][/tex]
[tex]\[ y = 2 \frac{1}{3} \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Substitute [tex]\( y = 2 \frac{1}{3} \)[/tex] back into the expression for [tex]\( x \)[/tex]:
[tex]\[ x = 6 - 2 \left(2 \frac{1}{3}\right) \][/tex]
[tex]\[ x = 6 - 2 \cdot \frac{7}{3} \][/tex]
[tex]\[ x = 6 - \frac{14}{3} \][/tex]
[tex]\[ x = 6 - 4 \frac{2}{3} \][/tex]
[tex]\[ x = 1 \frac{1}{3} \][/tex]
### Final Answer
Therefore, the solution to the system of equations is:
[tex]\[ x = 1 \frac{1}{3}, \quad y = 2 \frac{1}{3} \][/tex]
So, the correct answer is:
(C) [tex]\( x = 1 \frac{1}{3}, y = 2 \frac{1}{3} \)[/tex]
[tex]\[ \left\{\begin{array}{l} 7 x - y = 7 \\ x + 2 y = 6 \end{array}\right. \][/tex]
Let's solve the equations step by step.
### Step 1: Solve one of the equations for one variable
Let's solve the second equation for [tex]\( x \)[/tex]:
[tex]\[ x + 2y = 6 \][/tex]
[tex]\[ x = 6 - 2y \][/tex]
### Step 2: Substitute the expression into the other equation
Now, substitute [tex]\( x = 6 - 2y \)[/tex] into the first equation:
[tex]\[ 7(6 - 2y) - y = 7 \][/tex]
[tex]\[ 42 - 14y - y = 7 \][/tex]
[tex]\[ 42 - 15y = 7 \][/tex]
### Step 3: Solve for [tex]\( y \)[/tex]
[tex]\[ 42 - 15y = 7 \][/tex]
[tex]\[ -15y = 7 - 42 \][/tex]
[tex]\[ -15y = -35 \][/tex]
[tex]\[ y = \frac{-35}{-15} \][/tex]
[tex]\[ y = \frac{35}{15} \][/tex]
[tex]\[ y = \frac{7}{3} \][/tex]
[tex]\[ y = 2 \frac{1}{3} \][/tex]
### Step 4: Solve for [tex]\( x \)[/tex]
Substitute [tex]\( y = 2 \frac{1}{3} \)[/tex] back into the expression for [tex]\( x \)[/tex]:
[tex]\[ x = 6 - 2 \left(2 \frac{1}{3}\right) \][/tex]
[tex]\[ x = 6 - 2 \cdot \frac{7}{3} \][/tex]
[tex]\[ x = 6 - \frac{14}{3} \][/tex]
[tex]\[ x = 6 - 4 \frac{2}{3} \][/tex]
[tex]\[ x = 1 \frac{1}{3} \][/tex]
### Final Answer
Therefore, the solution to the system of equations is:
[tex]\[ x = 1 \frac{1}{3}, \quad y = 2 \frac{1}{3} \][/tex]
So, the correct answer is:
(C) [tex]\( x = 1 \frac{1}{3}, y = 2 \frac{1}{3} \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.